Edge : Turning Adversity into Advantage - Huang, Laura (College teacher) (New York : Portfolio/Penguin, 2020)
"Laura Huang, a preeminent Harvard Business School professor, shows that success is about gaining an edge: that elusive quality that gives you an upper hand and attracts attention and support. Some people seem to naturally have it. Now, Huang teaches the rest of us how to create our own from the challenges and biases we think hold us back, and turning them to work in our favor"
Introduction. Hard work, plus -- Enrich. Your basic goods ; Recognition of the incongruous ; The value of constraints ; Honing your gut feel and what you bring to the table -- Delight. The power of the unexpected ; Reflective improvisation ; Shaping and delighting in situ -- Guide. All the ways your diamond sparkles ; Turning biases and stereotypes in your favor ; Framing perceptions and attributions your way ; You need at least two points to create a trajectory -- Effort. Reinforcing your edge -- Edge principles.
Includes bibliographical references and index.
Keywords: Success; Success in business -- Psychological aspects; Performance -- Psychological aspects